2009
DOI: 10.1097/jnr.0b013e3181c122a3
|View full text |Cite
|
Sign up to set email alerts
|

Applying Watson's Nursing Theory to Assess Patient Perceptions of Being Cared for in a Multicultural Environment

Abstract: The caring behaviors based upon Jean Watson's theory were valued by Saudi patients irrespective of their cultural differences with the caregiver. However, the frequency of caring attended to by nurses in teaching/learning and helping/trust behavior subcategories were rated lower. Such is most likely the result of culture differences and language barriers existing between patients and nurses in Saudi Arabia. Results showed that the carative factors in Jean Watson's theory were also applicable to patients in Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…In this theory, nursing focused on helping patients achieve highest degree of harmony within seven most important caring behavior. (22) Regardingtosocio-demographic characteristicsof thenurses in table (1), thisstudyresultsshowedthattheageofnurses in study group for two thirdsofthem ranged between19-29years, half of them had Bachelor degree of nursing and one third had 1-5years of experience in pediatric critical care unit and that correlated withMizuno et al, who stated that nurses who hold a bachelor's, master's, or doctor degree perceived knowing the individual as more important than those who graduated only from nursing schools (23).In addition this also agree with study was done in king Saud University by Sulimanet al, who reported that the majority of nurses who participated their ages were 20-30, two thirds hold diploma degree in nursing and had 1-5 years of experience (24). Findings in the table (2) revealed that children ageswere more than half of them were less than 10 years old and more than one third of them has pneumonia so those children need more care and comfortable.…”
Section: Discussionmentioning
confidence: 67%
“…In this theory, nursing focused on helping patients achieve highest degree of harmony within seven most important caring behavior. (22) Regardingtosocio-demographic characteristicsof thenurses in table (1), thisstudyresultsshowedthattheageofnurses in study group for two thirdsofthem ranged between19-29years, half of them had Bachelor degree of nursing and one third had 1-5years of experience in pediatric critical care unit and that correlated withMizuno et al, who stated that nurses who hold a bachelor's, master's, or doctor degree perceived knowing the individual as more important than those who graduated only from nursing schools (23).In addition this also agree with study was done in king Saud University by Sulimanet al, who reported that the majority of nurses who participated their ages were 20-30, two thirds hold diploma degree in nursing and had 1-5 years of experience (24). Findings in the table (2) revealed that children ageswere more than half of them were less than 10 years old and more than one third of them has pneumonia so those children need more care and comfortable.…”
Section: Discussionmentioning
confidence: 67%
“…Work left undone involves instrumental care activities, such as oral care, mobility/turning, preventative activities, education of patients and information (Sasso et al., ). These findings are mirrored internationally, with under‐resourced countries faring much worse in general (Suliman, Welmann, Omer, & Thomas, ). In Italy, the average nurse/patient ratio is lower than the average European ratio; therefore, the extent of activities left undone is much higher than expected and emerging data confirm this (Sasso et al., ).…”
mentioning
confidence: 93%
“…However, the lack of professional caring of nurses leads to reduced wellbeing and the health of the patients. Therefore, nurses caring behaviors can influence patient satisfaction and perceived quality of nursing care [4,5]. A study showed that approximately 10-30% of general hospital nurses rated the quality of care on their ward as fair/poor and up to 50% felt that the quality of patient care had deteriorated [6].…”
Section: Introductionmentioning
confidence: 99%